Cardiac phenotypic spectrum of KCNT1 mutations. (4th December 2020) - Kohli, Utkarsh; Ravishankar, Chitra; Nordli, Douglas
Abstract: We report a 10-month-old girl with KCNT1 (c1420C > T; p. Arg474Cys, R474C) mutation-associated epileptic encephalopathy, systemic-to-pulmonary artery "collateralopathy", and intermittent QTc prolongation. Spontaneous regression of systemic-to-pulmonary artery collateral-mediated left heart dilation was noted in this patient, a finding which was ominous as it heralded the onset of severe pulmonary hypertension. The structural and electrical phenotypic features of KCNT1 mutation-associated heart disease, including the novel findings noted in our patient, are discussed in detail.